Matrix metalloproteinase 9 gene promoter region -1562 C/T single nucleotide polymorphism increases the susceptibility to hypertensive disorders of pregnancy: a meta-analysis - Yi Zhou; Ran Wang; Shi-Xian Chen; Li-Sheng Wu; Jun-Qing Zhu (IMR Press, 2021)
Hypertensive disorders of pregnancy (HDP) encompass a group of diseases. Single nucleotide polymorphisms (SNPs) are common in the matrix metalloproteinase 9 (MMP9) genes. The objective of this study was to analyse whether genetic polymorphisms in MMP9-1562 C/T alter the risk of HDP. Studies published up to October 2019 across PubMed, ScienceDirect, SpringerLink, and China National Knowledge Infrastructure database were searched. Case-control or cohort studies involving subtypes of HDP and distribution of genotypes and/or alleles within MMP9-1562 C/T in both patients and controls were selected. Number of genotypes and/or alleles for MMP9-1562 C/T polymorphisms were obtained and analyzed using Stata software. Eight published reports including 1300 HDP patients and 1612 controls were included in the meta-analysis. Results showed that a variant genotype and allele of MMP9-1562 C/T increased the risk of HDP, with pooled OR 1.50 (95% CI 1.16-1.95, P = 0.002) and 1.36 (95% CI 1.15-1.61, P < 0.001). Subgroup analyses showed that the variant genotype and allele of MMP9-1562 C/T also had increased risk of preeclampsia (OR = 1.48, 1.32; 95% CI 1.18-1.86, 1.08-1.62; P = 0.001, 0.007) and gestational hypertension (OR = 2.23, 1.88; 95% CI 1.52-3.28, 1.33-2.65; P < 0.001, < 0.001) in the fixed-effects models. This suggests that variant genotype (TT + TC) and allele (T) of MMP9-1562 C/T are associated with susceptibility of HDP, especially preeclampsia and gestational hypertension.